Achievements of Engineer, Entrepreneur and Teacher Jānis Baumanis (1878–1945) - Gaitniece, Lāsma; Zigmunde, Alīda (History of Engineering Sciences and Institutions of Higher Education, 2019)
The article is devoted to engineer, teacher and one of mayors of Lie- pāja City Municipality – Jānis Baumanis – who obtained university education not only at Riga Polytechnic Institute (RPI), but also at the University of Electricity (Ecole supérieure d’electricité) in Paris, France. The biography of J. Baumanis shows that he has been purposeful, feared no challenge and has repeatedly proved himself as entrepreneur establishing and successfully managing companies. These qualities also describe J. Baumanis as the Mayor of Liepāja City Municipality, but the desire to take initiative in implementing various, brave at that time, ideas were interfering, thus he held the position less than a year. After resigning, he left Liepāja city for Riga, where he worked for a company and turned to pedagogical work. The aim of the article is to summarize the life of J. Baumanis and to discover his achievements in various fields of activity.